A Review on Next-Generation Wildlife Monitoring using Environmental DNA (eDNA) Detection and Next-Generation Sequencing in Malaysia - OTHMAN, NURSYUHADA; KAVIARASU MUNIAN, KAVIARASU MUNIAN; HARIS, HIDAYAH; RAMLI, FARAH FARHANA; NUR HARTINI SARIYATI, NUR HARTINI SARIYATI; NAJMUDDIN, MOHD FAUDZIR; ABDUL-LATIFF, MUHAMMAD ABU BAKAR (2023)
The use of environmental DNA (eDNA) as the genetic tool to monitor biodiversity has been increasing across the world, including Malaysia. Over a decade, the technique has become widely used in wildlife conservation with the technologies called next-generation sequencing (NGS). Unfortunately, as one of the top megadiverse countries, Malaysia is still behind in this field since eDNA methods outperform traditional surveys. Hence, in this study, we analyzed the paper related to eDNA studies in Malaysia, which focused on wildlife monitoring. We conducted a systematic bibliographic search and quantitative review of studies published before June 2021 from Google Scholar and Scopus database. Forty published eDNA studies were found, and each paper was classified based on five themes (species identification, diet assessment, health monitoring, resolve taxonomic, whole-genome sequencing) according to the study analysis. This study aims to identify gaps in eDNA in Malaysia, which can later be useful for future conservation actions and development by applying technology in wildlife monitoring.